Awareness of Diabetic Patients towards Diabetes Mellitus: A Survey Based Study - Singla, Anjali; Sharma, Taruna; Kaeley, Nidhi (National Journal of Community Medicine, 2017)
Introduction: Increasing diabetes mellitus prevalence and associated health complications poses an enormous health burden. Awareness of this disease will play a vital role in its prevention and control. Also lack of adherence towards the management leads to poor glycemic control, thereby, increasing hazardous complications. The present study was conducted to assess the awareness of diabetes on various aspects among Type2 DM patients and to evaluate the treatment adherence. Methodology: This cross-sectional study was conducted on Type2DM patients visiting Diabetes OPD at HIMS, Dehradun over a period of six months. Demographic data and knowledge of participants on various aspects of DM was recorded using a structured and validated questionnaire. Descriptive statistics was used for data analysis. Results: Out of 100 patients, overall awareness was found to be average in 56% of the patients with majority being good (41%) regarding knowledge of DM while poor (38% and 58%) in complications and self-care practices respectively. Only 28% of the patients were adherent to their antidiabetic medications. Conclusion: Awareness among patients was found to be average but majority of them were non-adherent to their medications.